A new species of philichthyid copepod (Crustacea: Cyclopoida) parasitic on Stellifer spp. (Perciformes: Sciaenidae) from southeastern Brazil - Pombo, Maíra; Turra, Alexander; Paschoal, Fabiano; Luque, José Luis (Zootaxa, 2015)
A new species of copepod, Colobomatus stelliferi n. sp., belonging to the cyclopoid family Philichthyidae Vogt, 1877 is proposed based on female specimens collected from the mandibular canals of three species of sciaenid teleosts: Stellifer brasiliensis (Schultz) (type-host), S. rastrifer (Jordan) and S. stellifer (Bloch), collected in Caraguatatuba Bay, State of São Paulo, Brazil. The new species can be distinguished from its closest congeners by the absence of lateral processes in the genital somite, the presence of one cephalic process in the cephalosome and one pair of dorso-lateral processes on the fused pedigerous somites. This is the first species of Colobomatus Hesse, 1873 described as parasites of species of the teleost genus Stellifer.